IT asset management: refining the process to improve the asset center data accuracy: a case study in IT infrastructure of an oil and gas company located in Malaysia / Halimatun Aris - Aris, Halimatun (2010)
IT Asset Management is one of the key processes in any IT organizations who comply with IT Infrastructure Library (ITIL) standard. Over the years, the companies are growing and the IT assets have also increase. Therefore, management of the infrastructure assets is becoming more complex. There are a lot of researches that were conducted in the industry and have come up with the ideal framework on how to manage the assets. This study, however, is focusing on refining the current process framework with a proposed process which is rolled out in the sample company. The physical audit carried out in the data centers apparently do not match the asset data stored or tracked in the company's Configuration Management Database (CMDB). The KPI reports reported that the data accuracy initially was 67 percent which is unacceptable by the management. The low accuracy will definitely put the company at risk on noncompliance. Therefore, the. study was initiated to find out the possible causes of low data accuracy. An internal survey was conducted to find out level of awareness about IT Asset Management process. A project was then initiated to remediate the issues. The potential solutions were proposed to address the issue which includes a proposed process framework and controls over the processes through policy and communications. The proposed asset management process framework and its implementation through project management have improved the data accuracy of asset centre in the case company from 67% to 96.2%. This study not only improved the asset data center accuracy for better controls over IT expenses but also minimized the risk of non compliancy.